Adhesion to patient safety protocols in emergency care units - Danieli Parreira da Silva Stalisz da Paixão; Josemar Batista; Eliane Cristina Sanches Maziero; Francine Taporosky Alpendre; Marly Ryoko Amaya; Elaine Drehmer de Almeida Cruz
ABSTRACT Objective: To investigate compliance of national patient safety protocols in Emergency Care Units (UPA) of the Paraná State. Method: From April until September 2016, the exploratory stage of the action research was conducted on stratified sampling with 377 patients of eight units, with use of verification instrument of basic safety actions. Results: The absence of systematic identification of patients, fall risk assessment and signaling and development of pressure injuries were evidenced. We observed that 52.8% of parenteral solutions in use were not identified and that, in only 29.4% of the cases, the allergic condition was investigated. In 80.6% of the emergency units there was availability of alcoholic solution to hand hygiene. Conclusion: We concluded that the non-compliance of basic actions concerning patient safety exposes users to preventable adverse events and demands systematized actions to comply with government guidelines and promote quality of health assistance.